2017
DOI: 10.3390/molecules22111911
|View full text |Cite
|
Sign up to set email alerts
|

Ferulaldehyde Improves the Effect of Methotrexate in Experimental Arthritis

Abstract: Methotrexate (MTX) is still the gold standard for treatment of rheumatoid arthritis (RA). The therapeutic efficacy of low-dose of MTX can be increased by its combination with a natural substance, ferulaldehyde (FRA). The aim of this study was to evaluate the effect FRA and MTX administered alone or in combination in adjuvant arthritis. The disease was induced to Lewis male rats by intradermal injection, which contains a suspension of heat-inactivated Mycobacterium butyricum in incomplete Freund’s adjuvant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In addition, anthocyanins prevent the action of reactive oxygen species (ROS) generated by the administration of LPS, as observed by some authors [ 48 , 51 ]. Another polyphenol identified and worthy of interest is ferulaldehyde, a hydroxycinnamaldehyde found to be able to reduce the inflammatory response by reducing the release of cytokines, such as interleukin-1β and TNF-α, and by inhibiting the LPS-induced activation of the nuclear factor kappaB pathway in mice models [ 52 ]. Interestingly, some authors reported a synergistic effect of ferulaldehyde with Methotrexate in the therapy of inflammatory arthritis [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, anthocyanins prevent the action of reactive oxygen species (ROS) generated by the administration of LPS, as observed by some authors [ 48 , 51 ]. Another polyphenol identified and worthy of interest is ferulaldehyde, a hydroxycinnamaldehyde found to be able to reduce the inflammatory response by reducing the release of cytokines, such as interleukin-1β and TNF-α, and by inhibiting the LPS-induced activation of the nuclear factor kappaB pathway in mice models [ 52 ]. Interestingly, some authors reported a synergistic effect of ferulaldehyde with Methotrexate in the therapy of inflammatory arthritis [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another polyphenol identified and worthy of interest is ferulaldehyde, a hydroxycinnamaldehyde found to be able to reduce the inflammatory response by reducing the release of cytokines, such as interleukin-1β and TNF-α, and by inhibiting the LPS-induced activation of the nuclear factor kappaB pathway in mice models [ 52 ]. Interestingly, some authors reported a synergistic effect of ferulaldehyde with Methotrexate in the therapy of inflammatory arthritis [ 52 ]. Among other molecules, sinapine is one of the most representative phenolic acids in our samples, followed by m -coumaric acid and 2-hydroxybenzoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the role of 17-AAG was suggested not only to be preventive but also therapeutic. Some previous studies started the treatments of RA during induction of arthritis (45,55). Therefore, it is a limitation in this study that it could have been supplemented with experimental groups in which treatment would have been started after the onset of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant arthritis (AA) was induced by intradermal injection of Mycobacterium butyricum in incomplete Freund's adjuvant to male Lewis rats [36,37]. The experiment included healthy control animals (HC), arthritic animals (AA), and arthritic animals with administration of CoQ 10 (liquid liposomal CoQ 10 -LiQSorb ® ) in the oral daily dose of 100 mg/kg b.w.…”
Section: Experimental Design Of Adjuvant Arthritis With Administratiomentioning
confidence: 99%
“…(1) Not treated control groups (HC) (2) Arthritic animals not treated with HA (AA) Adjuvant arthritis was induced by a single intradermal injection of heat-inactivated Mycobacterium butyricum [36,37]. Blood was collected to obtain plasma and erythrocytes.…”
Section: Experimental Design Of Adjuvant Arthritis With Administratiomentioning
confidence: 99%